Reference compounds for characterizing cellular injury in high-content cellular morphology assays - Dahlin, Jayme L.; Hua, Bruce K.; Zucconi, Beth E.; Nelson, Shawn D.; Singh, Shantanu; Carpenter, Anne E.; Shrimp, Jonathan H.; Lima-Fernandes, Evelyne; Wawer, Mathias J.; Chung, Lawrence P. W.; Agrawal, Ayushi; O’Reilly, Mary; et al. (Nature communications, 2023)
Robust, generalizable approaches to identify compounds efficiently with undesirable mechanisms of action in complex cellular assays remain elusive. Such a process would be useful for hit triage during high-throughput screening and, ultimately, predictive toxicology during drug development. Here we generate cell painting and cellular health profiles for 218 prototypical cytotoxic and nuisance compounds in U-2 OS cells in a concentration-response format. A diversity of compounds that cause cellular damage produces bioactive cell painting morphologies, including cytoskeletal poisons, genotoxins, nonspecific electrophiles, and redox-active compounds. Further, we show that lower quality lysine acetyltransferase inhibitors and nonspecific electrophiles can be distinguished from more selective counterparts. We propose that the purposeful inclusion of cytotoxic and nuisance reference compounds such as those profiled in this resource will help with assay optimization and compound prioritization in complex cellular assays like cell painting. Cellular nuisance compounds are a burden in chemical biology and drug screening. Here the authors profile prototypical cytotoxic and nuisance compounds using the cell painting assay to systematically characterise cellular morphologies associated with compound-dependent cellular injury and nuisance activity.